2021
DOI: 10.3390/bios11100391
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Saturation Behavior by Pulse Oximetry in Female Athletes: Breaking Myths

Abstract: The myths surrounding women’s participation in sport have been reflected in respiratory physiology. This study aims to demonstrate that continuous monitoring of blood oxygen saturation during a maximal exercise test in female athletes is highly correlated with the determination of the second ventilatory threshold (VT2) or anaerobic threshold (AnT). The measurements were performed using a pulse oximeter during a maximum effort test on a treadmill on a population of 27 healthy female athletes. A common behavior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 112 publications
(146 reference statements)
0
24
0
1
Order By: Relevance
“…reported that there are two inflexion points at which SpO 2 decreases before AT. Additionally, the time until the second decrease in SpO 2 is strongly correlated with the time taken to reach AT 34 . The time until the second decrease in SpO 2 is also moderately correlated with VO 2max 34 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…reported that there are two inflexion points at which SpO 2 decreases before AT. Additionally, the time until the second decrease in SpO 2 is strongly correlated with the time taken to reach AT 34 . The time until the second decrease in SpO 2 is also moderately correlated with VO 2max 34 .…”
Section: Discussionmentioning
confidence: 98%
“…During incremental exercise, there are two inflection points at which the SpO 2 declines before AT. The time to the second decrease in SpO 2 and the time before AT is reached are closely correlated 34 . However, SpO 2 fluctuations during exercise are inconsistent and complex 34 .…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…There are some problems with the pulse wave sensor. The main categories of pulse wave pressure sensors include photoelectric sensors [ 14 , 15 , 16 , 17 ], piezoresistive sensors [ 18 , 19 ], ultrasonic sensors [ 20 ], and pressure sensors [ 21 ]. Photoelectric sensors, such as PPG sensors, which have made some notable progress [ 14 , 16 , 17 ], are susceptible to light interference from external sources, and cannot measure the trend of pulse wave pressure under continuously varying pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Часто спостерігаються явища дисонансу між нормальною макроперфузією (серцевий викид і артеріальний тиск) і гіпоперфузією тканин унаслідок дефектів мікроциркуляції в капілярному руслі [7,9]. Неінвазійна тканинна оксиметрія може допомогти вчасно виявити гемодинамічну нестабільність і непомітну гіпоксію, встановити толерантність до фізичних навантажень [10]. У педіатричній клінічній практиці найбільш часто пульсоксиметрія застосовується в неонатології, реаніматології, при пневмоніях, бронхіолітах, бронхіальній астмі та при апное різного генезу, а також у спортивній і шкільній медицині [8,[10][11][12].…”
unclassified